Three new free-living marine nematode species of Subsphaerolaimus Lorenzen, 1978, Halichoanolaimus de Man, 1886 and Belbolla Andrássy, 1973 from mangrove wetlands in Taiwan - Xiao, Yueping; Guo, Yuqing (Zootaxa, 2023)
Three new species of free-living marine nematodes belonging to the genera Subsphaerolaimus, Halichoanolaimus and Belbolla are described from the mangrove wetlands of western Taiwan Island. Subsphaerolaimus danshuiensis sp. nov. is characterized by a body length of 1345–1693 µm, subcephalic setae 22.5–65.0 µm long, cervical setae 16.5–33.0 µm long, an “L”-shaped spicule 66.9–76.4 μm long, and a gubernaculum with a caudally-dorsally directed apophysis 16.4–23.0 µm long. Halichoanolaimus sicaoensis sp. nov. is characterized by an amphidial fovea with 3.5–3.75 turns, a conico-cylindrical tail with the cylindrical portion approximately 3/4 of the total tail length, and 13–14 not equidistant papillose precloacal supplements. Belbolla forkyspicula sp. nov. is characterized by seven oesophageal bulbs, a short tail, a spicule with a proximal fork, and two winged supplements. Differentiating characteristics of the genera Subsphaerolaimus, Halichoanolaimus and Belbolla are provided. Types are deposited in the College of Fisheries, Jimei University.